Resourcing and the sustainability of Donor funded Potatoes Projects in Kabale District, Southwestern Uganda - Turyasingura, John Bosco; Moses, Agaba; Meza, Orach; Zombeire, Jotham; Kyabarongo, Benon (Special Journal of Politics and Economic Sustainability, 2022)
Background: Poor sustainability of funded potato projects occasioned by nonparticipation of potato farmers in local resourcing of funded potato projects continue to discourage donors from more investments because previously funded projects are not sustainable. Understanding the local participation-related project resourcing factors will be of profound significance in restoring the confidence of donors in the funding of potato projects. Objective: To determine the effect of participatory local resourcing on the sustainability of donor-funded potato projects in Kabale District. Materials and Methods: This study adopted a descriptive survey design, and it used potato farmers as the unit of analysis. Data were collected by administering questionnaires survey a sample population of 196 potato farmers. Structural equation modeling was used to test hypotheses. Results: Largely for all the paradigms of project resourcing (land, cost sharing, organic fertilizer and labour) donor funded potato projects have got challenges of sustainability Conclusion: Project resourcing affects the sustainability of donor-funded potato projects in Kabale District Recommendations: For effective sustainability of donor-funded potato projects, donors should allow potato project beneficiaries to participate in the project resourcing through the provision of land, inorganic manure, as well as cost-sharing so they know that, they have a stake in the project they are implementing